Predators of the Spiny Tailed Lizard (Uromastix hardwickii, Gray) - Chandra, Harish (Annals of Arid Zone, 2016)
Spiny tailed lizard is an important fauna of hot aid ecosystem. But it is fast getting extinct because of poaching and predators. Tribal people trap it for eating and supply these for laboratory use. Number of other mammals, reptiles and birds are predators. Behavior of these spiny tailed lizards and their predators is discussed. Key words: Spiny tail lizard, predators, behavior, trapping lizard, hunting.